Proyecto urbano: diseño de espacio público para el remate del plan parcial "triángulo de fenicia": Localidad de Santa Fé, Bogotá D.C. (2021)
This document has been made with the objective of projecting the urban design of action units for the partial plan "Triángulo de Fenicia" in the town of Santa Fe Bogotá D.C. Basic concepts are addressed from the main ecological structure, along with landscaping and public space, in addition, aspects such as social cohesion and the diversification of urban spaces in terms of their productive and meeting characteristics. Due to the consequences caused by COVID-19, it was considered pertinent to carry out an updated data survey, the restrictions dictated by the Mayor's Office of Bogotá with preventive isolation to mitigate the virus, made the inhabitants give a new use to the public space.